Measurement of the mechanical properties of nickel film based on the full-field deformation: An improved blister method - Wang, Z.; Ma, Z.; Zhou, Y.; Lu, Chunsheng (Elsevier B.V., 2013)
To characterize the mechanical properties of thin films, an improved blister method is proposed, which combines a digital speckle correlation method with the blister test. Based on this method, an experimental setup is developed to measure Young's modulus, residual stress, and interfacial adhesion energy of an electroplated nickel film. The results show that the improved blister method has the advantage of a high accuracy full-field measurement with the simple operation and low requirement on environments, which can be used to characterize the mechanical properties of films with various scales from laboratorial to industrial applications.